PENDAMPINGAN PENGELOLAAN SDM BERBASIS DIGITAL PADA UMKM UNTUK MENINGKATKAN DAYA SAING USAHA DI PAUH, KOTA PADANG - Febriani, Rina; Yulihardi, Yulihardi; Yoda, Tilawatil Ciseta; Reswita, Yefri; Afrida, Afrida (Komunitas Manajemen Kompetitif, 2024)
This community service program aims to improve the competitiveness of micro, small, and medium enterprises (MSMEs) in Pauh District, Padang City, through digital-based human resource management (HR) assistance. MSMEs play a strategic role in the local economy, but still face challenges in HR management, which is informal, undocumented, and limited use of technology. This situation results in low productivity, weak performance oversight, and limited adaptability to increasingly competitive business conditions. Based on a situational analysis, MSMEs in Pauh generally lack a structured system for recording attendance, assigning tasks, or evaluating performance. Furthermore, low digital literacy results in suboptimal use of technology in HR management. To address these challenges, this program is designed through a participatory approach, employing practice-based training and ongoing mentoring. Activities include mapping digital needs and readiness, training on the use of simple applications for recording and monitoring performance, and developing work standards and HR performance indicators. The mentoring is conducted in stages to enable MSMEs to implement the system independently. The program's outputs include improving the managerial capacity of MSMEs, implementing a digital-based HR system, developing modules, and developing scientific publications. This program is expected to sustainably drive productivity and digital transformation among MSMEs in Pauh